2009
DOI: 10.1017/s0022112009991753
|View full text |Cite
|
Sign up to set email alerts
|

The instability of a vortex ring impinging on a free surface

Abstract: Direct numerical simulation is used to study the development of a single laminar vortex ring as it impinges on a free surface directly from below. We consider the limiting case in which the Froude number approaches zero and the surface can be modelled with a stress-free rigid and impermeable boundary. We find that as the ring expands in the radial direction close to the surface, the natural Tsai–Widnall–Moore–Saffman (TWMS) instability is superseded by the development of the Crow instability. The Crow instabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…The study of vortex rings is well documented and includes: formation, 1-4 transport, [5][6][7] and interaction with solid walls [8][9][10][11] or free surfaces. [12][13][14][15] In most interaction experiments, the vortex ring is allowed to interact with solid or interfacial surfaces. [8][9][10][11][12][13][14][15] These interactions show that for non-permeable surfaces the vortex ring/boundary interaction can produce a range of dynamics depending on the strength of the vortex ring.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of vortex rings is well documented and includes: formation, 1-4 transport, [5][6][7] and interaction with solid walls [8][9][10][11] or free surfaces. [12][13][14][15] In most interaction experiments, the vortex ring is allowed to interact with solid or interfacial surfaces. [8][9][10][11][12][13][14][15] These interactions show that for non-permeable surfaces the vortex ring/boundary interaction can produce a range of dynamics depending on the strength of the vortex ring.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] In most interaction experiments, the vortex ring is allowed to interact with solid or interfacial surfaces. [8][9][10][11][12][13][14][15] These interactions show that for non-permeable surfaces the vortex ring/boundary interaction can produce a range of dynamics depending on the strength of the vortex ring. If a vortex is sufficiently strong, it will form a boundary layer on the surface that separates forming secondary vortex rings that orbit the primary vortex and then convect away from the wall.…”
Section: Introductionmentioning
confidence: 99%
“…The vortex rings are initially placed at H = 6R 0 . Following the previous treatment (Swearingen et al 1995;Archer et al 2010), periodic boundary conditions are used in the x-and y-directions. The computational domain chosen in the present study is sufficiently large to ensure that the effects of the periodicity are very small.…”
Section: Computational Overviewmentioning
confidence: 99%
“…The experimental study (Walker et al 1987) has revealed that the primary vortex ring no longer remains stable as it approaches the wall at high Reynolds number. When the Reynolds number is high enough, the interaction can lead to the breakdown of vortex rings and transition to turbulent state (Orlandi and Verzicco 1993;Archer et al 2010). Thus, the instability of vortex rings and transition to turbulence need to be investigated for a vortex ring impinging on a wall in the high-Reynolds-numberregime.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation